Prevalence of Helicobacter pylori infection among dyspepsia patients with mucosal lesion in tertiary care hospital - Yadav, Amit S.; Kulkarni, Umesh B.; Kumar, Bharat C.; Takalkar, Unmesh V. (International Surgery Journal, 2018)
Background: Helicobacter pylori (H. pylori), a curved rod shaped bacteria, is found to be associated with acid peptic disease patients, more in ulcer than non-ulcer, leading to a belief that H. pylori plays a role in its etiopathogenesis. In this study we examine the prevalence of H. pylori infection among dyspepsia patients with mucosal lesion. Methods: 300 patients of dyspepsia were enrolled in the study as per inclusion/exclusion criteria for a period of eight months. Enrolled patients were subjected to upper gastro-intestinal endoscopy and findings were recorded. Biopsy specimen taken from mucosal lesions were immediately inoculated on ‘RUT dry kit’ to test for H. pylori infection. Results: 234 out of 300 patients (78%) were found to be positive for H. pylori infection. The incidence of H. pylori infection was higher in patients with ulcer dyspepsia (88.46%) when compared to the patients with non-ulcer dyspepsia (72.44%). Conclusions: Prevalence of H. pylori infection was high and was found to have an association with ulcer dyspepsia allowing us to conclude that H. pylori may have a role in its etiopathogenesis.